Structural Equation Modeling Analysis of Purchase Behavior of Halal Products - Zuhri, Sarika; Ilyas, Ilyas; Erwan, Friesca; Syahputra, Rizki Agam; Sentia, Prima Denny; Noprita, Zikra (UIN Sunan Gunung Djati Bandung, 2023)
Indonesia is renowned for being home to the largest Islamic population globally, but the absence of a halal certification logo on products continues to be a cause for concern. For Muslim customers, their basic knowledge of halal ingredients written on the product is the only guide they can be relied on. Hence, it is crucial to understand the essential factors that influence their purchasing behavior regarding halal-certified products. This study uses the Theory of Planned Behavior (TPB) to examine Muslim customers' behavior, as a case study, in Banda Aceh. The TPB questionnaire, including attitude, subjective norm, perceived behavioral control, and purchase intention attributes, was distributed online to respondents in the Banda Aceh area using non-probability random sampling. Through Structural Equation Modeling (SEM) methodology and AMOS software, this research reveals a strong correlation between attitude and subjective norm with Muslim customers' purchasing intention. Moreover, purchasing intention shows a strong relationship with purchasing behavior. Consequently, attitude, subjective norm, and customers' intention are the critical factors that influence Muslim customers' behavior when purchasing halal-certified products in Indonesia.